Clinical Experience, Knowledge, Attitudes and Practice of Turkish Pediatric Dentists during the COVID-19 Pandemic - AKYÜZ, SERAP HATİCE (MDPI, 2021)
Background and Objectives: Coronavirus Disease 2019 (COVID-19) is a critical public health problem that has affected all fields, including dentistry. The dental management of children has become even more difficult during the COVID-19 pandemic. The purpose of this study was to evaluate the current knowledge, attitudes and practices of Turkish pediatric dentists who have been providing dental treatments to children during the COVID-19 pandemic. Materials and Methods: After receiving ethical approval, this cross-sectional study was conducted using the Google Forms online survey instrument. An online questionnaire link was sent to all the members of the Turkish Society of Paediatric Dentistry by e-mail and through social media. Statistical analyses were performed using descriptive statistics and Chi-square test; a p-value less than 0.05 was considered statistically significant. Results: A total of 200 pediatric dentists participated in this study and most of them (82%) only performed emergency dental treatments, whereas 18.5% performed both emergency and routine dental practices during the COVID-19 pandemic. The vast majority (72.5%) of pediatric dentists prescribed antibiotics and analgesics to their patients who were not cooperative with non-pharmacological behavior management techniques. The findings of the current study showed that the Turkish pediatric dentists had a good level of knowledge about COVID-19, satisfactorily conducted most of the infection control measures before and after the dental treatments, and attached importance to the use of PPEs; however, infection control measures during the dental treatments could be implemented better. Conclusions: Along with all precautions, the vaccination of healthcare workers and requesting a recent test result from patients showing a lack of COVID-19 disease before dental appointments could be used as effective infection control measures. Additionally, pediatric dentists should continue to follow local and universal guidelines, and education programmes should be frequently implemented in order to keep their COVID-19 management strategies up to date.
Keywords: anxiety; behavior management; children; coronavirus; COVID-19; infection control; oral health; pediatric dentistry; personal protective equipment; questionnaire; CORONAVIRUS DISEASE 2019; MAXILLOFACIAL SURGERY; INFECTION-CONTROL; IMPACT; ORTHODONTISTS; PERCEPTION; AWARENESS